The Cambridge companion to medieval philosophy - McGrade, Arthur Stephen (Cambridge University Press, 2003)
The Cambridge Companion to Medieval Philosophy takes its readers into one of the most exciting periods in the history of philosophy. It spans a millennium of thought extending from Augustine to Thomas Aquinas and beyond. It includes not only the thinkers of the Latin West but also the profound contributions of Islamic and Jewish thinkers such as Avicenna and Maimonides. Leading specialists examine what it was like to do philosophy in the cultures and institutions of the Middle Ages and engage with all the areas in which medieval philosophy flourished, including language and logic, the study of God and being, natural philosophy, human nature, morality, and politics. The discussion is supplemented with chronological charts, biographies of the major thinkers, and a guide to the transmission and translation of medieval texts. The volume will invaluable for all who are interested in the philosophical thought of this period.